Desarrollo e implementación de un directorio de empresas vía web 2.0 y recorrido virtual de atracciones turísticas como medio de información turística para las personas que visiten la ciudad de Loja. - Ruiz Riofrío, María del Carmen (2016)
This research work is executed in order to develop a Directory of Companies web route 2.0 and a virtual visit of tourist attractions and tourist information for people visiting the city of Loja. As a result of this investigation, we developed a web application that offers visiting tourist the following services: query information about a particular business or tourist attraction, find new places to visit, perform an efficient tourist information search in order to be able to communicate directly with the contact person for the place to visit, an easy-to-locate function thanks to Google Maps, which also allows access to a virtual tour of three tourist attractions in order to get a preview of the place to visit. Locally, it allows business people in Loja to visit the webpage, to learn news and to promote their companies or tourist places to whoever access this website. The methodology under use is ICONIX software development, fulfilling each of its phases: Analysis: It allowed us to know the current situation of how to promote the tourist sites of the city, and make a list of requirements for running our application. Design: Modeling operation and process diagrams to continue developing our web application. Implementation: By programming each of the diagrams made in the design phase. Test: Testing and maintenance checks were conducted to determine the quality of the software. The development tools used in developing this web application are open source and of free distribution. It uses a three-layers architecture to separate the business model of his access to the whole data. The application is hosted at a paid hosting that runs PHP with connection to MySQL database.